Business Strategy on Marketing Entrepreneurial Performance with Competitive Advantage as Intervening Case Study of UKM Ulos Fabric Craftsmen at the Department of SMEs and Cooperatives of North Sumatra Province - Nurafrina Siregar; Arlina Nurbaity Lubis; Endang Sulistya Rini; Beby Karina Fawzeea Sembiring (Journal of International Conference Proceedings, 2021)
The benchmark for the success of SMEs to be able to win in the competition is through marketing performance, especially because SMEs are currently becoming something important in supporting Indonesia's economic growth and the quantity of SMEs (the number of SMEs) is a big potential in the economy. Indonesia as a cultural country has the opportunity to develop products based on local wisdom. This research is a quantitative study, the population in this study is Ulos cloth SMEs assisted by the UKM and Cooperatives Service in North Sumatra Province. The population is 221 and the samples are spread over the area. Structural equation modeling (SEM) was used to analyze the data from this study.